Analisis Pengembangan Wilayah Berdasarkan Tingkat Sosial Ekonomi Di Provinsi Bengkulu Tahun 2023 - Saputro, Redo; Ayu Sejati, Martina (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
The social and economic sectors are need to be considered in assessing the level of development of a region. Bengkulu Province located on the west coast of the island of Sumatra has a contribution to Indonesia's GDP of 0.47%, which is a relatively small contribution of less than 1%. This aim of research is knowing the level of regional development in Bengkulu Province, by examining the social and economic sectors. The method is descriptive quantitative, quantitative analysis is used to analyze the level of regional development; then descriptive analysis is used to explain the phenomena that occur related to the level of regional development in Bengkulu Province. The level of regional development from the social sector, shows that most of them are in high qualifications (developed regions), this concludes that development related to the social sector is quite evenly distributed, only Lebong regency has a low classification level (underdeveloped) in contrast to the economic sector. That occurs in Bengkulu Province is mostly at the low classification level (underdeveloped regions), only Bengkulu City which is at high level, and North Bengkul Regancy with a medium level (developed). The Bengkulu Provincial Government needs to pay attention of areas with low classification (underdeveloped), especially in Lebong Regency with low classification (underdeveloped) in the social and economic sectors.